Enhancing Russian Language Learning Through Interactive Methods: A Synergistic Approach (Eurasian Scientific Herald, 2023)
This article explores the use of interactive methods in Russian language classes as a means to enhance language learning outcomes. Interactive methods incorporate various techniques that encourage active student participation, communication, and engagement, fostering a dynamic and constructive learning environment. By tapping into learners' intrinsic motivation and personal interests, interactive methods can effectively promote linguistic competence, cultural understanding, and overall language proficiency. This article presents a comprehensive synthesis of relevant literature, discussing the benefits, challenges, and practical implementation strategies of interactive methods in Russian language education. Findings reveal that interactive approaches play a significant role in enabling students to develop their language skills authentically, effectively, and meaningfully.